Aflatoxin M1 in soft and parmesan cheese by immunoaffinity column and liquid chromatography - Prado, Guilherme (2001)
Aflatoxin M1 was determined in Soft and Parmesan cheese by immunoaffinity column and liquid chromatography. Milk products such as cheese may be contaminated by aflatoxin M1 (AFM1) when dairy cattle have consumed feeds contaminated with aflatoxin B1 (AFB1). Samples of Soft and Parmesan cheese were collected in Belo Horizonte city, by the Inspection Service of Minas Gerais – Brazil. A purified extract was obtained by extraction with dichloromethane followed by a washing with n-hexane and immunoaffinity column clean-up. The quantification of AFM1 was done by high performance liquid chromatography (HPLC) using a fluorescence detector. AFM1 was detected in all soft cheese brands analysed, in concentrations ranging between 0.02 and 0.54 ng/g and mean level of 0.15 ng/g. In grated cheese, Parmesan variety, AFM1 was detected in 13 of 14 brands analysed (93%), in the range 0.04-0.30 ng/g with mean level of 0.14 ng/g.